Spatial patterns of the availability of community health centres in rural India, 2005 and 2019 - Vineet Kumar; Harpreet Singh; Avadhesh Kumar Meena; Sanjana Sharma (National Geographical Journal of India, 2023)
Community health centres, also known as community health services (CHSS), are located throughout the state and try to offer a wide variety of services and health promotion activities to the local population, especially for those who have the worst health or are at the risk of developing it and most deprived in context to economic and social needs. Community health centres are part of the rural health system. A considerable portion of the population lives in rural India. This study attempted to examine the changes in the availability and requirements of CHCs across the states in India from 2005 to 2019. Data is from Rural Health Statistics (RHS) (2005, 2019). MS Excel and ArcGIS are used for data analysis and mapping. Maharashtra (382), Rajasthan (298), Uttar Pradesh (294), Gujrat (271), and the lowest in Sikkim (4), Goa (5), and Tripura (9) had the highest number of CHCs in 2005, according to Indian Public Health Standards (IPHS). On the other hand, in 2019, Uttar Pradesh (679), Rajasthan (571), Tamil Nadu (385), and Orissa (377) had the highest number of CHCs, whereas the lowest was found in Sikkim (2), Goa (5), Mizoram (9). As per IPHS standards, Uttar Pradesh (917), Bihar (571), and West Bengal (420) had the highest requirements of CHCs in 2005, while the states with the highest requirements of CHCs in 2019 were Uttar Pradesh (857), Bihar (646), and Andhra Pradesh (491).